2018
DOI: 10.3389/fimmu.2018.02417
|View full text |Cite
|
Sign up to set email alerts
|

Human Monocytic Suppressive Cells Promote Replication of Mycobacterium tuberculosis and Alter Stability of in vitro Generated Granulomas

Abstract: Tuberculosis (TB) has tremendous public health relevance. It most frequently affects the lung and is characterized by the development of unique tissue lesions, termed granulomas. These lesions encompass various immune populations, with macrophages being most extensively investigated. Myeloid derived suppressor cells (MDSCs) have been recently identified in TB patients, both in the circulation and at the site of infection, however their interactions with Mycobacterium tuberculosis (Mtb) and their impact on gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 89 publications
(120 reference statements)
7
34
0
Order By: Relevance
“…Our study has evaluated bacterial internalization at a range of MOIs that includes low numbers of bacteria, and with a clinically relevant strain of E. coli responsible for invasive infections, such as sepsis and meningitis (Yao, Xie, & Kim, 2006). Additionally, two other studies have reported the internalization of M. tuberculosis and M. bovis BCG by MDSCs, again in agreement with our results (Agrawal et al, 2018; Magcwebeba et al, 2019; Martino et al, 2010). However, our study rigorously addressed the kinetics, frequency, and abundance of internalization using fluorescence microscopy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study has evaluated bacterial internalization at a range of MOIs that includes low numbers of bacteria, and with a clinically relevant strain of E. coli responsible for invasive infections, such as sepsis and meningitis (Yao, Xie, & Kim, 2006). Additionally, two other studies have reported the internalization of M. tuberculosis and M. bovis BCG by MDSCs, again in agreement with our results (Agrawal et al, 2018; Magcwebeba et al, 2019; Martino et al, 2010). However, our study rigorously addressed the kinetics, frequency, and abundance of internalization using fluorescence microscopy.…”
Section: Discussionsupporting
confidence: 93%
“…Davis and colleagues briefly suggested that MDSCs can phagocytose Escherichia coli ( E. coli ) particles in vitro ; however, the mechanistic details were not analyzed in depth (Davis, Silvin, & Allen, 2017). Additionally, two other studies reported that MDSCs can internalize Mycobacterium tuberculosis and Mycobacterium bovis Bacillus Calmette-Guerin (BCG), although the mechanisms, kinetics, and efficiency of internalization were not addressed (Agrawal et al, 2018; Magcwebeba, Dorhoi, & du Plessis, 2019; Martino et al, 2010). As such, our mechanistic understanding of direct MDSC interactions with bacterial pathogens has remained limited, and the consequences during infection have been unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of TG2 and the ensuing effect on autophagy, in addition with the capability of these drugs to increase the generation of glutathione-S-transferase (52), may have consequences on the pattern of chemokines and cytokines secreted by infected macrophages. To evaluate the activity of cystamine and cysteamine in a more complex system, involving multiple cell types, we implemented the ex vivo model of GLS (31,53). Treatment with cystamine or cysteamine of PBMCs infected with the Mtb H37Rv reference strain and the Mtb clinical strain H3 indicates a significant reduction in the total bacterial burden in GLS, although no major differences in GLS size were observed.…”
Section: Discussionmentioning
confidence: 99%
“…in vitro granuloma models have been developed to study M. tuberculosis [29,[68][69][70][71][72][73][74][75][76], M. leprae [77], M. bovis [78], M. massiliense [79], and Map [44]. Unique iterations of the M. tuberculosis model were used to investigate resuscitation from latency [69,76], consequences of macrophage polarization [71], and effects of cytokine suppression on granuloma development [74]. Granuloma models of other mycobacterial pathogens provide useful comparisons to M. tuberculosis with respect to bacterial survival, host response, and optimum MOI for cluster formation.…”
Section: Discussionmentioning
confidence: 99%
“…Granuloma models of other mycobacterial pathogens provide useful comparisons to M. tuberculosis with respect to bacterial survival, host response, and optimum MOI for cluster formation. Predictably, the MOI required to induce expression of Type 2-specific cytokines associated with reemergence is smaller in vitro with M. tuberculosis than other mycobacteria, as is the MOI associated with granuloma induction (1:200 [76]). Modelling M. bovis, a zoonotic cause of tuberculosis, researchers used MOIs of 1:1 to 5:1 to induce granuloma formation, seeming to contradict the observation that more virulent mycobacteria require lower MOI in these model systems [78].…”
Section: Discussionmentioning
confidence: 99%